2018
DOI: 10.1038/s41467-018-03465-9
|View full text |Cite
|
Sign up to set email alerts
|

Turning microplastics into nanoplastics through digestive fragmentation by Antarctic krill

Abstract: Microplastics (plastics <5 mm diameter) are at the forefront of current environmental pollution research, however, little is known about the degradation of microplastics through ingestion. Here, by exposing Antarctic krill (Euphausia superba) to microplastics under acute static renewal conditions, we present evidence of physical size alteration of microplastics ingested by a planktonic crustacean. Ingested microplastics (31.5 µm) are fragmented into pieces less than 1 µm in diameter. Previous feeding studies h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
316
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 737 publications
(357 citation statements)
references
References 52 publications
9
316
1
4
Order By: Relevance
“…Finally, synthetic particle presence in omnivorous life stages or species, especially loggerhead or ridley turtles, could originate through a pathway of trophic transfer from contaminated prey such as filter feeding invertebrates. Laboratory studies have shown trophic transfer of microplastics between invertebrates and within planktonic food webs (Dawson et al, ; Farrell & Nelson, ; Macali et al, ; Setälä et al, ). In addition, a recent study by Nelms et al () on grey seals ( Halichoerus grypus ) and wild‐caught Atlantic mackerel ( Scomber scombrus ) suggested that trophic transfer represents an indirect but potentially major pathway for any species whose feeding ecology involves the consumption of whole prey.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, synthetic particle presence in omnivorous life stages or species, especially loggerhead or ridley turtles, could originate through a pathway of trophic transfer from contaminated prey such as filter feeding invertebrates. Laboratory studies have shown trophic transfer of microplastics between invertebrates and within planktonic food webs (Dawson et al, ; Farrell & Nelson, ; Macali et al, ; Setälä et al, ). In addition, a recent study by Nelms et al () on grey seals ( Halichoerus grypus ) and wild‐caught Atlantic mackerel ( Scomber scombrus ) suggested that trophic transfer represents an indirect but potentially major pathway for any species whose feeding ecology involves the consumption of whole prey.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, synthetic particle presence in omnivorous life stages or species, especially loggerhead or ridley turtles, could originate through a pathway of trophic transfer from contaminated prey such as filter feeding invertebrates. Laboratory studies have shown trophic transfer of microplastics between invertebrates and within planktonic food webs (Dawson et al, 2018;Farrell & Nelson, 2013;Macali et al, 2018;Setälä et al, 2014). In addition, a recent study by F I G U R E 3 Type and colour of synthetic particles including microplastics identified from marine turtle gut content.…”
Section: Ingestion Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…One is possible translocation from HP cells to the hemolymph and then to other parts of the body such as the ovaries and gills, as reported in C. maenas (Farrell and Nelson, 2013;Watts et al, 2014). Alternatively, they might be fragmented into even smaller microor nano-particles as reported for millimeter diameter microplastic beads in Antarctic krill (Dawson et al, 2018). It is also possible that engulfed particles may end up in feces after ejection from the engulfing cells or from sloughing of those cells, as has been reported for B-cells that accumulate indigestible materials in vacuoles before they slough into the tubule lumen, to be replaced by new epithelial cells arising in the E-cell region of the HP (Hopkin and Nott, 1980).…”
Section: Discussionmentioning
confidence: 90%
“…The fragmentation of microplastics into nanoplastics (<100 nm in at least one dimension) is anticipated in marine environments (Andrady, ), with studies confirming the presence of submicron plastic particles in ocean water beginning to emerge together with advances in detection technology (Ter Halle et al ., ). In the marine environment, natural weathering effects caused by sand abrasion, waves and UV radiation (Gigault et al ., ), as well as digestive fragmentation (Dawson et al ., ) degrade plastic waste into plastic nanoparticles. The process of larger plastic pieces degrading into the nanoscale has been observed in simulated weathering conditions (Shim et al ., ; Lambert and Wagner, ).…”
Section: Introductionmentioning
confidence: 99%